The human activity as affective-cognitive unit: A historic-cultural approach - Martins, Lígia Márcia [UNESP]; Carvalho, Bruna [UNESP] (Universidade Estadual de Maringa, 2016)
This article puts in question the affectional-cognitive unit which sustains the human activity, with the purpose to light incorrectness of approaches which dichotomize reason and emotion. It asserts that such dissociations are founded in theorical-methodological principles which set bounds for explanations about the human psychism, so that the overcoming of referred dualisms puts on as a method matter. For making explicit that assertion, it resorted to Historic-Cultural Psychology, based on that it explains about the psychism as subjective image of objective reality, of Vygotskyan criticisms to Cartesian dualism and the need of a historic-cultural approach on emotion studies, intend to analyzing the human activity as a affectivecognitive unit and the imbricated relations that are waged, within it, among affections, emotions, feelings and thoughts. Once presented the interrelations between emotions and cognitions this exhibition argues that the concepts are necessary as a minimum unit of analysis both of thought and feelings.
Keywords: Activity; Affection; Cognition